Exploration and remediation ability test of indigenous bacteria from rice field pemalang regency on lead (Pb) contamined soil - Rahayu, Ahadiyat Yugi; Herliana, Okti; Hadi, Sapto Nugroho; Widyawati, Ida; Hanifa, Hana; Fauzi, Ahmad; Cahyani, Wilis; A, Ardiansyah; Sarjiya, Antonius; Widyarini, Indah; Widjanarko, Wisnu (Proceeding ICMA-SURE; Proceeding The 5th International Conference on Multidisciplinary Approaches for Sustainable Rural DevelopmentDO - 10.20884/2.procicma.2023.2.1.7911, 2023)
The research aims to obtain isolates and determine the morphological characteristics of bacteria that are resistant to Lead (Pb) contamination. The materials and tools used were soil from conventional rice farming land, Nutrient Agar (NA) medium, alcohol 70%, aquades, PbNO3 solution, aluminum foil, cling wrap, heat-resistant plastic, spiritus, physiological solution of 0.85% NaCl, autoclave, test tubes, petri dishes, erlenmeyer flasks, measuring cylinder, beaker glass, laminar air flow (LAF), shaker, magnetic stirrer, micropipette, refrigerator, analytical balance, ose needle, pH meter, vortex, ice box, shovel , tube racks, bunsen, stationery, labels, and other supporting materials and equipment. This research is a sampling research and continued with laboratory tests including bacterial isolation, colony count calculation and macromorphological characterization. The data obtained from morphological observations are presented in the form of descriptions, while quantitative data are presented in the form of numbers and are used as primary data. The results of isolating bacteria with NA medium added with 5 ppm lead, there are five bacterial isolates were selected, namely KMPb O, KT1Pb C, KT2Pb H, KB1Pb H, and KB2Pb K. Based on the TPC (Total Plate Count) test with a range of 30-300 colonies, the number of bacterial colonies ranged from 10,45 x 106 – 28,9 x 106 CFU/ml. The colony morphological characteristics of the five bacterial isolates were dominated by round in shape, smooth texture and flat elevation.